Perturbation of the molecular clockwork in the SCN of non-obese diabetic mice prior to diabetes onset. (25th November 2016) - Ingenwerth, Marc; Reinbeck, Anna Lena; Stahr, Anna; Partke, Hans-Joachim; Roden, Michael; Burkart, Volker; von Gall, Charlotte
ABSTRACT: Circadian disruption is associated with the development of diabetes. Non-obese diabetic (NOD) mice show abnormal diurnal profiles in energy balance and locomotor activity suggesting circadian misalignment. Therefore, we analyzed cFos and mPER1 as markers for rhythmic neuronal activity within the suprachiasmatic nucleus (SCN) of wildtype (WT) and non-diabetic (nNOD) as well as acutely diabetic NOD (dNOD) mice. cFos levels show a day/night difference in both WT and nNOD but not in dNOD. mPER1 levels did not show a day/night difference in both nNOD and dNOD. This suggests that disruption of SCN rhythmicity in NOD mice precedes the actual onset of diabetes.